Rancang Bangun Website Varia Info Pada Dinas Perhubungan Komunikasi Dan Informatika (DISHUBKOMINFO) Kabupaten Pacitan - Khamidah, Kun (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2012)
ABSTRACT: As an agency that is one element of government executor Pacitan, Department of Transportation Communication and Information Pacitan has the function and role of public service. The amount of important information that should be immediately communicated to the public Pacitan spread over 12 district requires a means of delivering information that can be accessed quickly by the entire community. Therefore, in practical work in the Department of Transportation Employment Practices and Information Technology communication Pacitan these researchers raised the topic